2014
DOI: 10.3389/fmicb.2014.00384
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus infection induces transcriptional and physical changes in developing maize kernels

Abstract: Maize kernels are susceptible to infection by the opportunistic pathogen Aspergillus flavus. Infection results in reduction of grain quality and contamination of kernels with the highly carcinogenic mycotoxin, aflatoxin. To understanding host response to infection by the fungus, transcription of approximately 9000 maize genes were monitored during the host-pathogen interaction with a custom designed Affymetrix GeneChip® DNA array. More than 4000 maize genes were found differentially expressed at a FDR of 0.05.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 88 publications
(117 reference statements)
2
77
0
Order By: Relevance
“…This may be due to an increase in the sugar content as the fungus increased amylase activity and catabolised complex carbohydrates [36]. Similarly, the minimal catabolism of the dough samples were close in features to the dent stage samples.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…This may be due to an increase in the sugar content as the fungus increased amylase activity and catabolised complex carbohydrates [36]. Similarly, the minimal catabolism of the dough samples were close in features to the dent stage samples.…”
Section: Discussionmentioning
confidence: 67%
“…This demonstrated that the spectral pre-treatment corrected for the differences due to path length alone and highlighted the differences in chemical composition [44,47]. The accumulation of free amino acids are reported in the less mature kernels compared to the more mature kernels [36,48]. Also, there is increased starch accumulation as the kernels mature [49,50].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Host resistance is a very attractive area on aflatoxin research, and various aspects of A. flavus-plant host interaction were investigated with special focuses on mechanisms resistant to fungal growth and aflatoxin production (Dolezal et al, 2014;Fountain et al, 2014;Hruska et al, 2014;Scarpari et al, 2014;Shan and Williams, 2014). In the up-to-date review on environmental influences on aflatoxin production on maize, Fountain et al (2014) detailed the history of research on this complex interaction and pointed out future directions for elucidating host resistance and susceptibility to A. flavus colonization in relation to abiotic stress such as drought and heat stresses, and oxidative stress in which aflatoxin may function as an antioxidant to the producing fungus.…”
mentioning
confidence: 99%
“…Their results highlighted the important role of maize oxylipins in driving secondary metabolism in A. flavus. In the microarray study to identify maize genes expressed during pathogen infection, Dolezal et al (2014) found that metabolic processes are linked to defense responses, which include physical changes within the kernel as well as a disruption in kernel development. Shan and Williams (2014) provided a concise but clear overview of current knowledge about quantitative trait loci of corn related to aflatoxin contamination and ongoing efforts in the development of resistant corn lines.…”
mentioning
confidence: 99%